THE PRESENT STATE OF BOTANICAL INVESTIGATIONS IN CÔTE D’IVOIRE - KOFFI, Kouao Jean; KOUASSI, Akossoua Faustine; ADOU YAO, Constant Yves; BAKAYOKO, Adama; IPOU, Ipou Joseph; BOGAERT, Jan (Biodiversity Informatics, 2015)
The aim of this present study is to summarize the current state of research on the flora of the Côte d’Ivoire from the SIG IVOIRE database to better direct future collection efforts. Herbarium specimen data used for this study covered the period from 1894 to 2000, and were assembled by 226 collectors. This database comprises 15,228 samples, grouped in 3621 species, 1371 genera, and 198 families. A grid system was used to cover the Ivorian territory at spatial resolution of 0.75° x 0.75°. Indices of evenness and completeness were calculated to characterize sampling and identify floristically well-known regions. The exploration of the Ivorian territory is far from uniform, such that some areas were more densely surveyed, but others partially or not at all. The regions of Grands Ponts, Agnéby-Tiassa, Loh-Djiboua, part of Gbèkè, Boukani, San Pedro and Cavally were floristically well known; environmentally, the largest gaps in coverge were in the mountains in western Côte d'Ivoire.